The Effect of Problem-Based Learning On Elementary Students’ Scientific Literacy: A Literature Review - Robiatul Adawiah; Aulia Aulia; Lutfiatussolihah Lutfiatussolihah (Indonesian Publication Center, 2026)
This research aims to comprehensively examine the effect of implementing the Problem-Based Learning (PBL) model on elementary school students' scientific literacy skills through a literature review approach. The method employed was a literature review of national and international journal articles published between 2016 and 2025. Data collection was conducted by searching databases such as Google Scholar, Garuda, DOAJ, and ERIC using keywords related to Problem-Based Learning and scientific literacy. A total of 18 articles meeting the inclusion criteria were analyzed using content analysis and thematic analysis techniques. The results of the review consistently indicate that the implementation of the PBL model has a positive and significant effect on enhancing elementary school students' scientific literacy. This improvement is demonstrated through differences in pre-test and post-test scores, N-Gain scores in the medium to high categories, and significant test results (p < 0.05). The scientific literacy indicators that showed improvement include the ability to explain scientific phenomena, evaluate and design scientific inquiries, interpret data and scientific evidence, and apply scientific concepts in everyday life. These findings affirm that the PBL model is an effective and relevant learning approach for improving elementary school students' scientific literacy and supporting the development of 21st-century skills.